2012
DOI: 10.1128/aac.00164-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a DHA-1-Producing Klebsiella pneumoniae Strain Involved in an Outbreak and Role of the AmpR Regulator in Virulence

Abstract: A clonal strain of Klebsiella pneumoniae producing the plasmid-encoded cephalosporinase DHA-1 was isolated from four patients admitted to the teaching hospital of Clermont-Ferrand, France, in 2006. It was responsible for severe infections in three of the patients; the fourth was colonized only in the gastrointestinal tract. The strain had at least two plasmids encoding resistance to antibiotics (quinolones, aminoglycosides, chloramphenicol, sulfonamides, and trimethoprim), as shown by disk diffusion assay, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 49 publications
1
26
1
Order By: Relevance
“…Our results are comparable with those of other studies in Spain, China, and France, which observed the diffusion of DHA-1 plasmid-mediated cephalosporinases in K. pneumoniae strains (Hennequin et al, 2012;Guo et al, 2012;Tobes et al, 2013). There are few studies concerning the cephalosporinases AmpC diffusion in this species in Algeria.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are comparable with those of other studies in Spain, China, and France, which observed the diffusion of DHA-1 plasmid-mediated cephalosporinases in K. pneumoniae strains (Hennequin et al, 2012;Guo et al, 2012;Tobes et al, 2013). There are few studies concerning the cephalosporinases AmpC diffusion in this species in Algeria.…”
Section: Discussionsupporting
confidence: 82%
“…Sahly et al (2008) have also observed an upregulation of type 3 fimbriae expression, pivotal for biofilm formation, upon acquisition of ESBL (SHV-12)-encoding plasmids. Moreover, plasmids encoding cephalosporinases have been demonstrated to get transcriptional factors, that is, AmpR, involved in the upregulation of capsule synthesis and resistance to killing by serum as well as in the modulation of biofilm formation and expression of type 3 fimbriae, thus increasing virulence of K. pneumoniae (Hennequin et al 2012b;Compain et al 2014).…”
Section: Relative Expressionmentioning
confidence: 99%
“…More specifically, ampR from a plasmid containing the DHA-1 enzyme in a clinical strain of K. pneumoniae was shown to be involved in capsule synthesis and the derived serum resistance, biofilm formation, type 3 fimbrial gene expression, adhesion to cells in culture, as well as colonization of the gastrointestinal tract in mice (287). These results add strength to the previously mentioned idea on the wide pleiotropic power of ampR (and other LysR regulators) to regulate not only intrinsic or horizontally acquired ␤-lactamases expression but also many other bacterial processes, including virulence.…”
Section: Effects Of Horizontally Acquired ␤-Lactamases On Fitness Andmentioning
confidence: 99%